Recommendations for Self-Report Outcome Measures in Vulvodynia Clinical Trials. Issue 8 (August 2017) - Pukall, Caroline F.; Bergeron, Sophie; Brown, Candace; Bachmann, Gloria; Wesselmann, Ursula
Abstract : Objectives: Vulvodynia (idiopathic chronic vulvar pain) is a prevalent condition associated with significant and negative impacts in many areas of function. Despite the increased research interest in vulvodynia in recent years, recommendations for outcome measures for use in clinical trials are missing. The purpose of this paper, therefore, was to provide recommendations for outcome measures for vulvodynia clinical trials so that consistent measures are used across trials to facilitate between-study comparisons and the conduct of large multicenter trials, and to improve measurement of the multiple dimensions of vulvodynia. Methods: Given that provoked vestibulodynia (PVD)—characterized by provoked pain localized to the vaginal opening—is the most common subtype of vulvodynia and the current main focus of clinical trials, this paper focused on recommended outcome measures in PVD clinical trials. The framework used to guide the selection of outcome measures was based on the one proposed by the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT). Results: The IMMPACT framework provided a well-suited guideline for outcome measure recommendations in PVD clinical trials. However, given the provoked presentation of PVD and the significant impact it has on sexuality, modifications to some of the IMMPACT recommendations were made and specific additional measures were suggested. Discussion: Measures that are specific to vulvovaginal pain are ideal for adoption in PVD clinical trials, and many such measures currently exist that allow the relevant IMMPACT domains to be captured.